Maxwell-Bloch Equations without Spectral Broadening: Gauge Equivalence, Transformation Operators and Matrix Riemann-Hilbert Problems - Filipkovska, M.S.; Kotlyarov, V.P.; Melamedova, E.A. (Журнал математической физики, анализа, геометрии, 2017)
A mixed initial-boundary value problem for nonlinear Maxwell{Bloch (MB) equations without spectral broadening is studied by using the inverse scattering transform in the form of the matrix Riemann{Hilbert (RH) problem. We use transformation operators whose existence is closely related with the Goursat problems with nontrivial characteristics. We also use a gauge transformation which allows us to obtain Goursat problems of the canonical type with rectilinear characteristics, the solvability of which is known. The transformation operators and a gauge transformation are used to obtain the Jost type solutions of the Ablowitz-Kaup-Newel-Segur equations with well-controlled asymptotic behavior by the spectral parameter near singular points. A well posed regular matrix RH problem in the sense of the feasibility of the Schwartz symmetry principle is obtained. The matrix RH problem generates the solution of the mixed problem for MB equations.